Multidisciplinary Approach in Vaccination of a Child with Food Allergy: Clinical Case - Vera G. Kalugina; Marina V. Fedoseenko; Anna A. Alekseeva; Kamilla E. Efendieva; Julia G. Levina; Tatiana A. Kaliuzhnaia; Svetlana V. Tolstova; Elena A. Vishneva; Leyla S. Namazova-Baranova (Union of pediatricians of Russia, 2022)
Children with chicken egg protein allergy are denied performing vaccination against measles, mumps, influenza in Russian Federation thus far, thus it is unreasonable. This article presents a clinical case of 2 years 6 months old boy with cow's milk protein allergy symptoms and high levels of specific IgE antibodies (sIgE) to chicken egg protein. He was unreasonably denied performing vaccination against measles, rubella, and mumps at the place of residence according to false interpretation of the clinical situation as the absolute contraindication for vaccination. Lately, the child was successfully vaccinated against these infections at Research Institute of Pediatrics and Children's Health in "Central Clinical Hospital of the Russian Academy of Sciences". The examination dynamics is presented, as well as the data on the extended allergy diagnostics of separate components via the ISAC allergochip. Finally, the prognosis on food allergy resolution and recommendations on nutrition and further vaccination were given for this patient.